2013
DOI: 10.1063/1.4811864
|View full text |Cite
|
Sign up to set email alerts
|

10,000 – A reason to study granular heat convection

Abstract: Abstract. In sheared granular media, particle motion is characterized by vortex-like structures; here this is demonstrated experimentally for disks system undergoing indefinite deformation during simple shear, as often imposed by the rock masses hosting earthquake fault gouges. In traditional fluids it has been known for years that vortices represent a major factor of heat transfer enhancement via convective internal mixing, but in analyses of heat transfer through earthquake faults and base planes of landslid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Solid particle motion enhanced cold and hot particles mixing, hence increasing the heat transfer rate. A lot of research about packed bed also showed that only fluid flow rate increase also leads to enhancement of ETC [46,50,[52][53][54][55].…”
Section: Effect Of Gas Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid particle motion enhanced cold and hot particles mixing, hence increasing the heat transfer rate. A lot of research about packed bed also showed that only fluid flow rate increase also leads to enhancement of ETC [46,50,[52][53][54][55].…”
Section: Effect Of Gas Motionmentioning
confidence: 99%
“…This model is probably the earliest method for granular ETC evaluation. It represents a series model that considers the system as a parallel-serial thermal resistance system [53] which got its popularity in the early age.…”
Section: Models Of Etcmentioning
confidence: 99%